A Review of Termite Pheromones: Multifaceted, Context-Dependent, and Rational Chemical Communications - Mitaka, Yuki; Akino, Toshiharu (Frontiers in Ecology and Evolution, 2021)
Termite colonies, composed of large numbers of siblings, develop an important caste-based division of labor; individuals in these societies interact via intra- or intercaste chemical communications. For more than 50 years, termites have been known to use a variety of pheromones to perform tasks necessary for maintenance of their societies, similar to eusocial hymenopterans. Although trail-following pheromones have been chemically identified in various termites, other types of pheromones have not been elucidated chemically or functionally. In the past decade, however, chemical compositions and biological functions have been successfully identified for several types of termite pheromones; accordingly, the details of the underlying pheromone communications have been gradually revealed. In this review, we summarize both the functions of all termite pheromones identified so far and the chemical interactions among termites and other organisms. Subsequently, we argue how termites developed their sophisticated pheromone communication. We hypothesize that termites have diverted defensive and antimicrobial substances to pheromones associated in caste recognition and caste-specific roles. Furthermore, termites have repeatedly used a pre-existing pheromone or have added supplementary compounds to it in accordance with the social context, leading to multifunctionalization of pre-existing pheromones and emergence of new pheromones. These two mechanisms may enable termites to transmit various context-dependent information with a small number of chemicals, thus resulting in formation of coordinated, complex, and rational chemical communication systems.